Assemblage and diversity analysis of butterfly species in relation to climatic conditions in some tropical habitats: optimization through artificial neural network model - Subha Shankar Mukherjee; Asif Hossain (Journal of Ecology and Environment)
Background: Biodiversity serves as the foundation for ecosystems and the functional roles of species that supply services to human well-being. The functional roles of species in a region can be assessed by estimating biological diversity. Due to their presence in both aquatic and terrestrial ecosystems, insects have been used as model organisms in several studies, and among insects, butterfly species are considered important model organisms for both ecology and conservation biology. Butterfly species are very sensitive to changes in climatic conditions and serve as important bioindicators for both habitat and climate. For this reason, estimation of butterfly diversity at the spatio-temporal scale is important. On a spatial scale, habitat heterogeneity is believed to be the important factor that plays an important role in maintaining butterfly species diversity, while the differences in diversity of butterfly species on a temporal scale can be linked with climatic conditions both at the regional and local scales. Results: The present study aimed to determine the effects of habitat characteristics and climatic conditions on the diversity of butterfly species in Purulia, India. A total of 83 butterfly species were found during the present study. Out of 83 butterfly species, Nymphalidae dominate over other families (28 species; 33.73%). The highest species richness was observed in the Ajodhya Hill region (61 species), followed by Garh Panchakot (54 species) and Leprosy Mission (47 species). The relative abundance and butterfly species richness differed between sites with different habitat characteristics. Maximum temperature serves as the most sensitive variable for species richness and is negatively related. Conclusions: From this study, it is evident that different habitats in Purulia can sustain a diverse variety of butterfly species, but significant conservation effort is required. So, considering Purulia as a model area, steps must be taken to maintain habitat heterogeneity and local climatic conditions for sustaining ecosystem services provided by butterfly species.